Education Instruments for Foodborne outbreaks prevention - Viegas, Silvia (2018)
Introduction: Foodborne outbreaks (FBO) represent an important cause of morbidity and mortality worldwide. Their epidemiologic investigation allows us to identify their risk and contributive factors as scientific evidence to work preventively with the younger population, increasing their health literacy on FBO prevention. Purpose: Develop food safety educational materials for high school, for teacher’s level, to contribute to FBO prevention.